Influence of content marketing on consumer behavior in veterinary services in Chiclayo - Vallejos Villanueva, Angel Alberto; Valderrama Puscan, Marlon Walter; Panta Merino, Monica Esther (LACCEI, 2025)
The purpose of this scientific article is to analyze the influence of content marketing on consumer behavior in veterinary services in the city of Chiclayo, taking as a case study the “Clinica y Spa Mascotas”. The research was based on a quantitative approach, applied type, with a non-experimental, cross-sectional and correlational design. A validated and reliable questionnaire was used to survey 180 clients. The results showed that there is a significant correlation between content marketing and consumer behavior, explaining 81.5% of its variability. It is concluded that an adequate digital strategy focused on valuable content and loyalty has a positive impact on customer perception, purchase decision and loyalty